Sevoflurane and isoflurane anesthesia induce redox imbalance, but only sevoflurane impairs vascular contraction - Rocha, Thalita L. A. [UNESP]; Borges, Teubislete F. [UNESP]; Rodrigues, Serginara D. [UNESP]; Martins, Laisla Z. [UNESP]; da Silva, Maria L. S. [UNESP]; Bonacio, Gisele F.; Rizzi, Elen; Dias-Junior, Carlos A. [UNESP] (Wiley, 2023)
Volatile anesthetics may cause vascular dysfunction; however, underlying effects are unclear. The aim of the present study was to investigate whether sevoflurane and isoflurane affect vascular function, nitric oxide (NO) bioavailability, and biomarkers of oxidative stress and inflammation. Wistar rats were divided into three experimental groups: Not anesthetized (control group) or submitted to anesthesia with isoflurane (Iso group) or sevoflurane (Sevo group). Hemodynamic parameters were monitored during anesthesia, and blood gas values and biochemical determinants were analyzed. Isometric contractions were recorded in aortic rings. Vasoconstriction induced by potassium chloride (KCl) and phenylephrine (Phe) were measured. No differences in hemodynamic parameters and blood gasses variables were observed. Impaired KCl and Phe-induced contractions were observed in endothelium-intact aorta of Sevo compared to Iso and Control groups. Redox imbalance was found in Sevo and Iso groups. Reduced NO bioavailability and increased activity of matrix metalloproteinase 2 (MMP-2) were observed in Sevo, but not in the Iso group. While reduced IL-10 and IL-1β were observed in Sevo, increases in IL-1β in the Iso group were found. Sevoflurane, but not isoflurane, anesthesia impairs vasocontraction, and reduced NO and cytokines and increased MMP-2 activity may be involved in vascular dysfunction after sevoflurane anesthesia.
Keywords: isoflurane; metalloproteinase; nitric oxide; sevoflurane; vascular function